Accountability: The Case of Accreditation of British Columbia’s Public Schools - Maxwell, T. W. (Canadian Journal of Education/Revue canadienne de l’éducation, 1996)
Post-industrial governments are demanding higher levels of accountability, not least in the education sector. Accountability in British Columbia’s schools was initially based upon inspectors’ reports. It evolved into an accreditation process. This article analyzes the British Columbia public school accreditation process using an expanded model of account- ability based on Lundgren (1990). The main subjects of discussion are the difficulty of accreditation serving two audiences, and the nature of the accreditation manual. Les gouvernements post-industriels exigent une responsabilisation accrue, y compris et surtout dans le secteur de l’éducation. L’obligation de rendre compte dans les écoles de la Colombie-Britannique a d’abord été fondée sur les rapports des inspecteurs, puis a progressivement donné lieu à un processus d’agrément. Cet article analyse le processus d’agrément des écoles publiques de la Colombie-Britannique en faisant appel à un modèle élargi de responsabilité issu de Lundgren (1990). Les principaux thèmes abordés sont la difficulté de l’agrément en présence de deux auditoires ainsi que la nature du manuel d’agrément.